2006
DOI: 10.1258/095646206778145686
|View full text |Cite
|
Sign up to set email alerts
|

Confidentiality is essential if young people are to access sexual health services

Abstract: A survey was undertaken to determine the importance of confidentiality of sexual health clinics to young people, and their preferences for service provision. A questionnaire was given to school attenders in year 9 (age 13-14 years) at four comprehensive schools. Class leaders assisted students with literacy or language difficulties. Two hundred and ninety five questionnaires were distributed and all were returned (male 143 (48.5%), female 152 (51.5%). In all 199 (67.5%) had never used sexual health services. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 7 publications
2
33
0
1
Order By: Relevance
“…If we turn to studies on adolescents in general in the absence of those specifically on YPISC, these suggest that confidentiality in relation to sexual health is extremely important to teenagers (Thomas, Murray, & Rogstad, 2006) and fears around confidentiality breaches are the principal deterrent to their seeking sexual health advice (Royal College of General Practitioners' Adolescent Health Group, 2011). Thomas et al's (2006) UK-based survey of 13-14 year olds found that over half rated confidentiality as most important feature of health services and the vast majority reported being more likely to use a service if it were confidential.…”
Section: Discussionmentioning
confidence: 99%
“…If we turn to studies on adolescents in general in the absence of those specifically on YPISC, these suggest that confidentiality in relation to sexual health is extremely important to teenagers (Thomas, Murray, & Rogstad, 2006) and fears around confidentiality breaches are the principal deterrent to their seeking sexual health advice (Royal College of General Practitioners' Adolescent Health Group, 2011). Thomas et al's (2006) UK-based survey of 13-14 year olds found that over half rated confidentiality as most important feature of health services and the vast majority reported being more likely to use a service if it were confidential.…”
Section: Discussionmentioning
confidence: 99%
“…Mobile phones are able to provide confidential and non-judgemental support, which is essential for a sexual health intervention. 12 Interactive support can be delivered at any time and in any location, ensuring privacy, which is especially important for young people. Behaviour change techniques (BCTs) used in effective face-to-face interventions can be modified for delivery via text message.…”
Section: Fundingmentioning
confidence: 99%
“…This suggests that adolescents who are comfortable with parental knowledge of their sexual activity still value confidentiality in health care related to sexual issues. In this study, regard- [7,8]. Consequently it is not surprising that the lack of confidentiality imposed when parental consent is required is a significant barrier to enrollment in STI-related research.…”
Section: Discussionmentioning
confidence: 88%